Fundamental Determinants of Inequality and the Role of Government - Tanzi, Vito (IMF Working Papers; Working Paper, 1998)
This paper discusses the fundamental determinants of inequality. These are identified as world or market forces, social norms, ownership of real and human capital, and the role of government. The change in the relative role of these factors in determining inequality during economic development is analyzed.